Project #NuKapav: a Mauritian service-learning case study - Hardin-Ramanan, Sarita; Balla Soupramanien, Loga Devi; DeLapeyre, David (Emerald, 2018)
Purpose - Prompted by the enlarging skills gap between the university graduate and the desired employee in Mauritius, the Charles Telfair Institute embarked its students on the #NuKapav project for an authentic work integrated learning (WIL) experience which endeavours to fight for the societal inclusion of Persons with Disabilities. The purpose of this paper is to examine the impact of this service-learning project on the students from professional, civic engagement and social justice perspectives.